PERANAN TOKOH ADAT DALAM MELESTARIKAN ADAT LAMPUNG SAI BATIN DI KABUPATEN PESISIR BARAT PROVINSI LAMPUNG - Abdul Halim; Berchah Pitoewas; Edi Siswanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The challenge faced is the potential extinction of Adat Lampung Sai Batin in Pesisir Barat Regency due to social, economic, and technological changes that threaten the continuity of cultural traditions. This condition has reduced cultural understanding and practice, while widening the gap between the younger generation and traditional leaders, which may lead to the loss of traditional values. The main objective of this study is to preserve and maintain the authenticity of Adat Lampung Sai Batin through the involvement of traditional leaders in reviving customary practices, strengthening community understanding, and passing on Lampung cultural heritage to future generations. The targets include increasing community awareness and participation, empowering traditional leaders as agents of cultural preservation, and developing educational programs to improve public understanding of Adat Lampung Sai Batin. The methods used include training, workshops, awareness campaigns, and collaboration with local government to integrate Lampung cultural elements into preservation efforts.